Expression of transcription factors in MEN1-associated pancreatic neuroendocrine tumors - Yasutaka Takeda (Endocrinology, Diabetes & Metabolism Case Reports, 2017)
MEN1-associated pancreatic neuroendocrine tumors (pNETs) may potentially express distinct hormones, but the mechanism has not been elucidated. Transcription factors such as MafA and Pdx1 have been identified to lead to beta cell differentiation, while Arx and Brn4 to alpha cell differentiation in developing pancreas. We hypothesized those transcription factors are important to produce specific hormones in pNETs, similarly to developing pancreas, and examined the expression of transcription factors in a case of MEN1 who showed immunohistological coexistence of several hormone-producing pNETs including insulinoma. A 70-year-old woman was found to manifest hypoglycemia with non-suppressed insulinemia and hypercalcemia with elevated PTH level. She was diagnosed as MEN1 based on the manifestation of primary hyperparathyroidism, pituitary adenoma and insulinoma, with genetic variation of MEN1 gene. She had pylorus-preserving pancreaticoduodenectomy because CT scan and SACI test indicated that insulinoma was localized in the head of the pancreas. Histopathological finding was MEN1-associated NET, G1. Interestingly, immunohistological examination of the resected pancreas revealed that two insulinomas, a glucagon-positive NET and a multiple hormone-positive NET coexisted. Hence, we examined the expression of transcription factors immunohistochemically to elucidate the role of the transcription factors in MEN1-associated hormone-producing pNETs. We observed homogeneous expressions of MafA and Pdx1 in insulinomas and Arx in glucagon-positive NET, respectively. Moreover, multiple hormone-positive NETs expressed several transcription factors heterogeneously. Collectively, our results suggested that transcription factors could play important roles in the production of specific hormones in MEN1-associated pNETs, similar to islet differentiation.